Graduation Profile Mapping: A Study of Bibliometric Analysis of the Curriculum - Irawan, Muhammad Dedi (International Conference on Sciences Development and Technology, 2022)
Mapping is very necessary in making the right decision based on the scientific mapping of each. This is very useful in mapping graduate profile relationships. The aim of the study was to map elective courses in the curriculum of the Information Systems Study Program at the State Islamic University of North Sumatra based on bibliometric analysis. The research process is carried out by analyzing graduate profiles, then the analysis process uses the publish or perish application with google scholar study sources. The results of the analysis are then processed using the Mendeley application to filter the details of each source and finally using the VoS Viewer application to visualize the mapping results.